2008
DOI: 10.1002/cpp.578
|View full text |Cite
|
Sign up to set email alerts
|

Physiological reactivity to stress and parental support: comparison of clinical and non‐clinical adolescents

Abstract: An Alarm Stress Task was developed to study affect regulation in the context of parent-child interactions in adolescents (mean age = 12.72, standard deviation = 2.06) with (n = 20) and without (n = 20) mental health problems. Changes in heart rate (HR), preejection period (PEP) and respiratory sinus arrhythmia (RSA) were used as indicators of affect regulation. HR increased, and PEP and RSA decreased signifi cantly in reaction to a suggested failure on a simple task, indicating that this procedure induced affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“…For example, Egizio et al (2008) found that women who reported more positive social functioning also exhibited slight increases in heart rate variability during an acute stressor. More directly related, children experienced significant increases in heart rate variability after being reunited with a parent following a stressful lab experience (Willemen et al, 2008). In short, higher heart rate variability (HF-HRV) has been commonly associated with healthier functioning, both physically and socially.…”
Section: Social Support and Physiological Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Egizio et al (2008) found that women who reported more positive social functioning also exhibited slight increases in heart rate variability during an acute stressor. More directly related, children experienced significant increases in heart rate variability after being reunited with a parent following a stressful lab experience (Willemen et al, 2008). In short, higher heart rate variability (HF-HRV) has been commonly associated with healthier functioning, both physically and socially.…”
Section: Social Support and Physiological Stressmentioning
confidence: 99%
“…Lepore, Allen, & Evan, 1993;Thorsteinsson & James, 1999), reduced hypothalamic-pituitary-adrenal (HPA) axis reactivity (Heinrichs, Baumgartner, Kirschbaum, & Ehlert, 2003), increased parasympathetic nervous system reactivity (e.g. Willemen, Goossens, Koot, & Schuengel, 2008) and better immune function (see Uchino, Cacioppo, and Kiecolt-Glaser (1996) for a review).…”
Section: Social Support and Physiological Stressmentioning
confidence: 99%
“…Alarm Stress Task (AST). The AST (Willemen et al., 2008) is a controlled paradigm in which the adolescents have to lie quietly on their beds in their own bedroom for 21 minutes, while their physiological activity is measured by an ambulatory monitoring system (see below). The experimenter suggests that any movement will set off an alarm signal and could spoil the measurement.…”
mentioning
confidence: 99%
“…Following each alarm, there is a three‐minute reunion with the parent. The AST has been shown to induce significant changes in sympathetic and parasympathetic reactivity in adolescents with and without psychopathology and to elicit variation in secure‐base behaviour (Willemen et al., 2008). Information about the duration of the episodes is given in Figure 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation